Biomechanical comparison of transosseous re-fixation of the deep fibres of the distal radioulnar ligaments versus deep and superficial fibres: a cadaver study - Spies, Christian; Unglaub, Frank (International orthopaedics, 2016)
Purpose: We hypothesized that the re-fixation of the deep and superficial fibres of the distal radioulnar ligaments provide improved stability compared to reconstruction of the deep fibres alone. Methods: Fourteen fresh-frozen cadaver upper extremities were used for biomechanical testing. Transosseous re-fixation of the deep fibres of the distal radioulnar ligaments alone (single mattress suture group; n = 7) was compared to the transosseous re-attachment of the deep and superficial fibres (double mattress suture group; n = 7). Cyclic load application provoked palmar translation of the radius with respect to the rigidly affixed ulna. Creep, stiffness, and hysteresis were obtained from the load-deformation curves, respectively. Testing was done in neutral forearm rotation, 60° pronation, and 60° supination. Results: The re-fixation techniques did not differ significantly regarding the viscoelastic parameters creep, hysteresis, and stiffness. Several significant differences of one cycle to the consecutive one within each re-fixation group could be detected especially for creep and hysteresis. No significant differences between the different forearm positions could be detected for each viscoelastic parameter. Conclusions: The re-fixation techniques did not differ significantly regarding creep, hysteresis, and stiffness. This means that the additional re-attachment of the superficial fibres may not provide greater stability to the DRUJ. Bearing in mind that the study was a cadaver examination with a limited number of specimens we may suppose that the re-attachment of the superficial fibres seem to be unnecessary. A gradual decline of creep and hysteresis from first to last loading-unloading cycle is to be expected and typical of ligaments which are viscoelastic.